Synergistic effects of dopamine D2-like receptor antagonist sulpiride and β-blocker propranolol on learning in the carousel maze, a dry-land spatial navigation task - Prokopová, Iva; Bahník, Štěpán; Doulames, Vanessa; Valeš, Karel; Petrásek, Tomáš; Svoboda, Jan; Stuchlík, Aleš (Pharmacology, biochemistry and behavior, 2012)
Spatial navigation attracts the attention of neuroscientists as an animal analogue of human declarative memory. The Carousel maze is a dry-land navigational paradigm, which proved to be useful in studying neurobiological substrates of learning. The task involves avoidance of a stable sector on a rotating arena and is highly dependent upon the hippocampus. The present study aims at testing hypothesis that sulpiride (a centrally-active dopamine D2-like receptor antagonist) and propranolol (a beta-blocker) impair spatial learning in the Carousel maze after combined systemic administration. These doses were previously shown to be subthreshold in this task. Results showed that both substances affected behavior and significantly potentiated their negative effects on spatial learning. This suggests central interaction of both types of receptors in influencing acquisition of this dynamic-environment task.
Keywords: antagonisté dopaminu D2; Animals; Psychomotor Performance; beta blokátory; sulpirid; Rats, Long-Evans; Receptors, Dopamine D2; psychomotorický výkon; Propranolol; antagonisté dopaminu; Dopamine Antagonists; Spatial Behavior; potkani Long-Evans; Male; propranolol; Drug Synergism; Sulpiride; krysa rodu Rattus; synergismus léků; Adrenergic beta-Antagonists; Maze Learning; mužské pohlaví; zvířata; receptory dopaminu D2; bludiště - učení; Rats; prostorové chování; Dopamine D2 Receptor Antagonists